The Saint of Dragons - Hightman, Jason (New York : Eos, 2004)
After a lonely childhood at the Lighthouse School for Boys, thirteen-year-old Simon learns that he is descended from a medieval dragonslayer, and that his father needs his help to face the last of these evil monsters.
Keywords: George, -- Saint, -- d. 303 -- Fiction; Dragons -- Fiction; Fathers and sons -- Fiction; Knights and knighthood -- Fiction